2005
DOI: 10.2174/1389200054633899
|View full text |Cite
|
Sign up to set email alerts
|

CAR, The Continuously Advancing Receptor, in Drug Metabolism and Disease

Abstract: The detoxification and elimination of potentially toxic foreign and endogenous compounds depends on the concerted action of xenobiotic metabolizing enzymes. Nuclear hormone receptors (NHRs) have emerged as key regulators of the expression of these enzymes and his review focuses on the xenosenor CAR (Constitutive Androstane Receptor, NR1I3). CAR is highly expressed in the liver and the small intestine, two key tissues expressing xenobiotic metabolizing enzymes, and mediates the induction of their expression by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
134
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(137 citation statements)
references
References 101 publications
3
134
0
Order By: Relevance
“…5,[16][17][18] In this study, we found that ethanol could also increase the expression of CAR target genes CYP2B10 and CYP2E1 via a CAR-dependent manner. However, the increase in the magnitude of CAR activation is not strong as the increase of the target gene expression is not robust.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…5,[16][17][18] In this study, we found that ethanol could also increase the expression of CAR target genes CYP2B10 and CYP2E1 via a CAR-dependent manner. However, the increase in the magnitude of CAR activation is not strong as the increase of the target gene expression is not robust.…”
Section: Discussionmentioning
confidence: 51%
“…What is the reason that only a small population has a higher risk of alcoholic liver diseases? Considering that many prescription drugs and environment contaminants can activate CAR, 5 we propose that the simultaneous exposure to the CAR activators and alcohol consumption may greatly enhance individual susceptibilities to alcohol-induced liver damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAR, upon activation by therapeutics such as PB, induces a large set of genes that encode for drugmetabolizing enzymes with the CYP2B enzymes being the classic CAR-regulated genes, thus increasing hepatic capability for drug metabolism and excretion (2)(3)(4). CAR plays the essential role in PB-induced promotion of hepatocellular carcinoma development (5).…”
mentioning
confidence: 99%
“…Two types of CAR activators can translocate CAR into the nucleus; one type, represented by PB, consists of a number of therapeutic drugs that indirectly translocate CAR into the nucleus without any direct binding. The other type includes various xenobiotics, acting as ligands, which directly bind to CAR, such as 1,4-bis-[2-(3,5-dichloropyridyloxy)]benzen (TCPOBOP) and 6-(4-chlorophenyl)imidazo [2,1-b] [1,3]thiazole-5-carbaldehyde O- (3,4-dichlorobenzyl)oxime (CITCO) for mouse and human CARs, respectively (9,10). Regardless of the types, the molecular mechanism of how these activators translocate CAR into the nucleus has been a mystery since CAR was first characterized as a xenobioticactivated nuclear receptor (1).…”
mentioning
confidence: 99%